2020
DOI: 10.4149/bll_2020_002
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial transplantation of neural stem cells improve functional recovery after transient ischemic stroke in adult rats

Abstract: OBJECTIVES: The neural stem cell transplantation has been proposed as alternative therapy to promote functional recovery after various neurological disorders. The aim of this study was to evaluate the effect of intra-arterial transplantation of adult neural stem cells on improving local brain ischemia injuries. MATERIALS AND METHODS: In this study, 32 male Wistar rats were used. Ischemia was induced using a middle cerebral artery obstruction with monofi lament nylon suture. Neural stem cells were isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In contrast, Andres et al (2011) revealed simultaneous decrease of infarct size and neurological deficit at day 3 post-stroke in mice receiving mouse postnatal C-C chemokine receptor 2 (CCR2 + / +) NSC. Similar results were reported by Kondori et al (2020) after adult rat NSC transplantation. Though exact causes of the described differences are not clear, they are probably due to the variations of the properties of transplanted cells themselves that is related to their origin and culture conditions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, Andres et al (2011) revealed simultaneous decrease of infarct size and neurological deficit at day 3 post-stroke in mice receiving mouse postnatal C-C chemokine receptor 2 (CCR2 + / +) NSC. Similar results were reported by Kondori et al (2020) after adult rat NSC transplantation. Though exact causes of the described differences are not clear, they are probably due to the variations of the properties of transplanted cells themselves that is related to their origin and culture conditions.…”
Section: Discussionsupporting
confidence: 90%
“…A number of preclinical studies have demonstrated that neural stem/precursor cells (NSC/NPC) derived from the other sources (from adult or fetal brain tissues, embryonic stem cells, induced pluripotent stem cells) have also promoted functional recovery after intra-arterial transplantation into animal models of stroke ( Andres et al, 2011 ; Doeppner et al, 2015 ; Rosenblum et al, 2015 ; Kondori et al, 2020 ). However, the extent of the positive effects have been somewhat different.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 2, many studies have assessed NSC transplantation to treat ischemic brain injury in animal models. The initial hypotheses were based on the assumption that NSCs would replace lost neurons and restore connections in neuronal circuitry [94][95][96][97][98][99][100][101][102][103][104][105][106]. Indeed, analysis of graft-derived neuronal cells using immuno-electron microscopy and electrophysiological recording demonstrated increased connectivity, showing that NSCs could develop into functioning neurons to contribute to improved recovery from stroke and brain injury in rats [107,108].…”
Section: Experimental Studies Investigating Neural Stem Cells Transplmentioning
confidence: 99%
“…Although transplanted NSCs are expected to differentiate into various neural cells rather than other stem cells, it remains unclear to what extent this contributes to functional recovery. The current understanding is that transplanted NSCs likely prevent neuronal apoptosis, exert immunomodulatory effects inside and outside the brain, increase endogenous neuronal regeneration and angiogenesis, and inhibit glial scar formation mainly via paracrine and autocrine secretion of various neurotrophic factors rather than differentiation [ 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 109 , 110 ] ( Table 2 ).…”
Section: Neural Stem Cellsmentioning
confidence: 99%
“…To adequately investigate stem cell therapies for neurological diseases in preclinical studies, it is very important to develop imaging technologies that are able to evaluate disease progression by “chasing” (i.e., tracking or monitoring) transplanted stem cells in recipients. The pathology of stroke and regeneration by transplanted stem cells develop through either endogenous or exogenous mechanisms, which can be assessed using various imaging technologies, including traditional tissue staining, immunohistochemistry, autoradiography, electrophysiological analysis, and molecular biological methods [ 115 , 116 ].…”
Section: Imaging Techniques For Stem Cell Therapymentioning
confidence: 99%